1996
DOI: 10.1021/bi9522514
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Isofagomine and Its Derivatives As Potent Glycosidase Inhibitors

Abstract: A pseudo-aza-monosaccharide and several pseudo-aza-disaccharide compounds were constructed based on replacement of the anomeric carbon with a nitrogen and the ring oxygen with a carbon. The inhibition constants of these compounds toward five different glycosidases, alpha-glucosidase, beta-glucosidase, isomaltase, alpha-mannosidase, and glucoamylase, were obtained. Isofagomine, the pseudo-aza-monosaccharide, shows a broad spectrum of strong inhibition against glycosidases. It is the most potent inhibitor of bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 112 publications
(56 citation statements)
references
References 32 publications
3
52
0
1
Order By: Relevance
“…1). Sierks and colleagues showed that IFG inhibits yeast isomaltase, with a K i of 7.2 μM, a value somewhat lower than the 100 μM IC50 value we determined for the human enzyme [26]. The failure of IFG and NB-DNJ to inhibit lactase is consistent with previous work showing that galactose analogs such as NB-DGJ but not glucose analogs are good inhibitors of this enzyme [9].…”
Section: Discussionsupporting
confidence: 89%
“…1). Sierks and colleagues showed that IFG inhibits yeast isomaltase, with a K i of 7.2 μM, a value somewhat lower than the 100 μM IC50 value we determined for the human enzyme [26]. The failure of IFG and NB-DNJ to inhibit lactase is consistent with previous work showing that galactose analogs such as NB-DGJ but not glucose analogs are good inhibitors of this enzyme [9].…”
Section: Discussionsupporting
confidence: 89%
“…Benzyl-b-d-arabinopyranoside 12 [9] and benzyl-3,4-isopropylidene-b-d-arabinopyranoside 14 [10] gave the expected acetals 13 and 15 in 44 % and 41 % yield, respectively. Again instability of the benzylidene compounds accounts for the diminished yields.…”
Section: H and 13mentioning
confidence: 94%
“…bon and the anomeric carbon with a nitrogen [Dong et al, 1996], is a stronger inhibitor of ß-glucosidase, glucoamylase and isomaltase than deoxynojirimycin but its effect on GTF-I is slight and isofagomine does not seem to have potential for application as a GTF inhibitor.…”
Section: Inhibition Of Soluble Gtfmentioning
confidence: 99%
“…Glucamine was obtained from Tokyo Kasei Kogyo (Chuo-ku, Tokyo, Japan). Isofagomine was a kind gift of M. Bols [Dong et al, 1996]. Acarbose, N-dodecyldeoxynojirimycin, the amine hydrofluorides Dectaflur (9-octadecenylamine-hydrofluoride), Olaflur (N)-octadecyltrimethylamine-N,N,N)-tris (2-ethanol)-dihydrofluoride) and Xidecaflur (bishydroxylated oleyl amine hydrofluoride) were provided by GABA International, Munchenstein, Switzerland.…”
Section: Inhibitorsmentioning
confidence: 99%